AKREDITASI MADRASAH - Mulyono, Mulyono (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2010)
Quantitatively, amount of madrasah which increasing since decade 1990-an, hence policy require to be strategic to the make-up of its quality. One of the effort with believed to become strategic step develop;build quality of madrasah is require to perform of accreditation of madrasah periodical. performed of the accreditation program expected can reach standard is quality of which is specified and in turn can improve quality of good madrasah at quality of quality and also institute all educative participant to be able to reach efficacy of education. Accreditation system play role which do not only is important, but strategic also. That strategic role for example is, First: giving comprehensive information to society (stakeholders) concerning certain madrasah. Second, as starting point all educationist and all builder of madrasah in analysing and giving solution to problem of faced by madrasah. Third, as a means of operation of quality. Accurate information which got from accreditation will become starting point to pertinent madrasah to conduct internally of review able to be made by directive in make-up of quality.Keywords: Accreditation, Madrasah